Adsorption Isotherm and Kinetics Studies of Chemical Modified Waste Corn Stalk by Urea and Microwave for Removal of Lead(II) - Pan, Qingshan; Li, Jianqiang; Chen, Xianlan; Shi, Ling; Yan, Heping; Zhou, Bo; Xu, Shijuan; Wang, Jing; Gou, Gaozhang; Wu, Na; Huang, Dushu; Long, Yunhui; et al. (Asian Journal of Chemistry, 2015)
Corn stalk modified by urea and microwave was investigated as an adsorbent for Pb(II) removal from aqueous solution. The preparing parameters on mass percent gain of modified corn stalk are analyzed using response surface methodology. The effects of pH and modified corn stalk dose on the Pb(II) removal process were studied by batch methods. The maximum adsorption capacity of Pb(II) onto modified corn stalk was found to be 12.78 mg/L. The adsorption isotherms were analyzed using the Langmuir and Freundlich isotherms. The results showed that the adsorption process was well described by Langmuir isotherm model with correlation coefficients (R) of 0.99998 for Pb(II) adsorption. Kinetic studies revealed that the adsorption process followed pseudo second order model.